The Effect of Oral Gabapentin and Pregabalin as a Prodrug in Pain Control after Orthopedic Surgery on the Upper Limb: A Double-Blind Parallel Randomized Clinical Trial Study - Lida Nouri; Rana Roshanfekr; Azam Biderafsh; Reza Pakzad; Hamed Azadi (Anesthesiology Research and Practice)
Objective. To compare the effects of oral gabapentin (GBP) and pregabalin (PGB) in pain control after orthopedic surgery on the upper limb. Methods. In this double-blind randomized clinical trial study, 80 patients who were the candidates for elective orthopedic surgery on one of the parts of the upper limb were divided into two groups using balance-block randomization. For the first group, a 150 mg capsule of PGB (one hour before the surgery) and for the second group, a 300 mg capsule of GBP (two hours before the surgery) were prescribed. Patients were subjected to standard monitoring at the beginning and during surgery. The pain scores were evaluated at before surgery, in PACU (postanesthesia care unit), and 6 and 12 hours after the surgery by VAS (visual analog scale). Results. In this study, 37 subjects were allocated to each group. The participation rate was 92.5%. The mean with 95% confidence interval (CI) of pain scores over 4 times in the PGB group was 4.03 (3.25–4.79), 3.76 (3.02–4.49), 3.65 (3.06–4.23), and 3.41 (2.88–3.93) and in the GBP group was 4.08 (3.33–4.83), 2.78 (2.11–4.45), 2.3 (2.05–2.54), and 2 (1.51–2.50), respectively. The within-group comparisons showed a significant decrease in the pain score over time (P<0.001). Also, the between-group comparison showed significant differences between the two groups in terms of pain score (P<0.001). In the end, results showed that there is a significant interaction between time and intervention for pain score (P=0.042). Conclusion. Although two medicines led to a reduction in the pain score, but the rate reduction in the PGB group was significantly more than that in the GBP group. This trial is registered with IRCT20211013052759N1.